2017
DOI: 10.21873/anticanres.11905
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between HSP90/topoisomerase I Immunophenotype and the Clinical Features of Colorectal Cancers in Respect to KRAS Gene Status

Abstract: Our results revealed that cooperation between HSP90 and Topo I expression exists in CRCs, independently of KRAS gene status, suggesting that co-expression of both proteins might be considered as a double target on individual tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Notably, mutated RAS may predict sensitivity to HSP90 inhibition due to serine threonine kinase 33-dependent mechanisms in CRC cell lines 14 . According to the tumor tiuuse of CRC, another clinical study has confirmed that a positive correlation exists between KRAS mutation and HSP90 expression 15 . These studies echo the findings of our study.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, mutated RAS may predict sensitivity to HSP90 inhibition due to serine threonine kinase 33-dependent mechanisms in CRC cell lines 14 . According to the tumor tiuuse of CRC, another clinical study has confirmed that a positive correlation exists between KRAS mutation and HSP90 expression 15 . These studies echo the findings of our study.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, the association between the HSP family and KRAS has been previously reported. Bar et al reported that HSP90 expression is associated with KRAS mutation and worse clinical parameters in CRC (22). The HSP family, including HSP27, may play certain roles in association with KRAS, which warrants further investigation.…”
Section: Model Of Acquired Resistance To 5-fluorouracil (5-fu) In Wid...mentioning
confidence: 99%